Decomposed Impact of Democracy on Indonesia’s Economic Growth - Hardi, Irsan; Ringga, Edi Saputra; Fijay, Ade Habya; Maulana, Ar Razy Ridha; Hadiyani, Rahmilia; Idroes, Ghalieb Mutig (Ekonomikalia Journal of Economics, 2023)
Indonesia's democratic performance is still classified as a 'moderate' and 'flawed democracy' according to the latest report, even though the ongoing progress of national democracy continues to advance every year. This study addresses the issue by offering a more comprehensive perspective and distinguishes itself by employing a decomposition approach that incorporates 25 indicators of the Indonesian democracy index to assess their individual effects on economic growth, which no prior Indonesian study has explored. The study classifies these indicators into six distinct categories: freedom and civil rights issues, discrimination issues, political and electoral issues, social and cultural issues, law and justice issues, and demonstration and community participation issues. The findings reveal that five out of the six categorized indicators have a crucial role and significantly impact economic growth. This evidence suggests that policymakers should prioritize a multifaceted approach, which includes bolstering the protection of civil rights and freedoms, combating discrimination, as well as reforming electoral and political processes. If implemented with transparency and inclusivity, this approach can pave the way for a more robust and prosperous democracy, leading to better and sustainable economic growth in Indonesia.